Legal Regulation of Migration Processes in Modern Russia - G. I. Tyumentseva (Сибирское юридическое обозрение, 2014)
The article deals with the analysis of the legal mechanisms of migration policy realization proceeding within the framework of the Conception of the state migration policy of the Russian Federation for the period till 2025. The author stresses the necessity of more effective legal regulation of migration processes enabling to defend the interests of migration relations subjects (state, individual, society).